Reliability and validity of a method for the assessment of sport rock climbers' isometric finger strength - Torr, O.; Randall, T.; Knowles, R.; Giles, D.; Atkins, S. (The Journal of Strength and Conditioning Research, 2022)
Isometric strength of the finger flexors is considered to be one of the main physical determinants of sport rock climbing performance. We set out to determine the test-retest reliability and criterion validity of a low resource maximal isometric finger strength (MIFS) testing protocol that uses a pulley system to add or remove weight to/from a climber's body. To determine test-retest reliability, 15 subjects' MIFS was assessed on 2 occasions, separated by a minimum of 48 hours. Body mass and maximum load were recorded on both occasions. Intra-class correlation coefficients (ICCs) between visits for all variables were very good (ICC > 0.91), with small bias and effect sizes—particularly when expressed as a percentage of body mass (ICC = 0.98, 95% confidence interval 0.93-0.99). To determine the criterion validity of MIFS and climbing ability, data of 229 intermediate to higher elite climbers were compared. Pearson's product moment correlations demonstrated good agreement, again particularly between total load when expressed as a percentage of body mass and climbing performance (r = 0.421-0.503). The results illustrate the sensitivity of a simple test for the determination of MIFS in intermediate to height elite climbers from an ecologically valid, climbing specific test that only requires equipment found at most climbing walls. This low resource test protocol for the assessment of isometric finger strength has wide-reaching utility, for instance when assessing strength before and after a training intervention or when prescribing load intensities for exercises aimed at improving maximal finger strength.